Advancing Competency-Based Medical Education: A Charter for Clinician-Educators - Carraccio, Carol; Englander, Robert; Van Melle, Elaine; Ten Cate, Olle; Lockyer, Jocelyn; Chan, Ming-Ka; Frank, Jason R; Snell, Linda S (Academic medicine, 2016)
The International Competency-Based Medical Education (ICBME) Collaborators have been working since 2009 to promote understanding of competency-based medical education (CBME) and accelerate its uptake worldwide. This article presents a charter, supported by a literature-based rationale, which is meant to provide a shared mental model of CBME that will serve as a path forward in its widespread implementation.At a 2013 summit, the ICBME Collaborators laid the groundwork for this charter. Here, the fundamental principles of CBME and professional responsibilities of medical educators in its implementation process are described. The authors outline three fundamental principles: (1) Medical education must be based on the health needs of the populations served; (2) the primary focus of education and training should be the desired outcomes for learners rather than the structure and process of the educational system; and (3) the formation of a physician should be seamless across the continuum of education, training, and practice.Building on these principles, medical educators must demonstrate commitment to teaching, assessing, and role modeling the range of identified competencies. In the clinical setting, they must provide supervision that balances patient safety with the professional development of learners, being transparent with stakeholders about level of supervision needed. They must use effective and efficient assessment strategies and tools for basing transition decisions on competence rather than time in training, empowering learners to be active participants in their learning and assessment. Finally, advancing CBME requires program evaluation and research, faculty development, and a collaborative approach to realize its full potential.